الحماية القانونية للأصناف النباتية الجديدة : دراسة مقارنة - د. هالة مقداد أحمد الجليلي (PROSPECTIVE RESEARCHES, 2023)
The present research tackles the subject of the legal protection of the new plant classes. The research is divided into two sections. Section One divides into three subsections ; the first includes the notion of the new plant classes and their exceptions, the second states the objective conditions to protect the new class, while the third displays the formal condition of that protection. Section two includes two subsections ; the former mentions the legal effects of the protection of the new plant class, while the latter shows the evaluation of the legal system of the new plant class. Finally, the study comes up with a set of conclusions related to the subject.